Detecting Fraud Reviews of Apps Using Sentiment Analysis - Sabeena, S (International Journal of Computer Sciences and Engineering, 2019)
Sentiment analysis is one of the main tasks of Natural Language Processing (NLP). This analysis had gained more attention in recent years. In this paper, we tackled the problem of sentiment polarity categorization as one of the fundamental problems of sentiment analysis. A general process is proposed with detailed descriptions. Data used are online product reviews collected from Amazon.com. Experiment for sentence-level categorization and review-level categorization are performed with best outcomes. Finally, we give insight into our future work on sentiment analysis.